The Differences SGPT Levels Using Immediately Monoreagent And Delayed For 5 Days At Room Temperature - Salma Yuki Anisa Putri; Hari Saktiningsih (Jurnal Biologi Tropis, 2026)
SGPT (Serum Glutamic Pyruvic Transaminase) is a liver enzyme that plays an important role in assessing hepatocellular damage. The stability of reagents, especially monoreagents consisting of a mixture of reagent 1 and reagent 2, affects the accuracy of laboratory test results. Delaying the use of monoreagent at room temperature may influence the enzymatic activity of SGPT. This study aims to determine the difference in SGPT levels between the monoreagent used immediately and the monoreagent delayed for 5 days at room temperature.This study used an experimental design with 16 serum samples from second-year students in the Diploma III Medical Laboratory Technology Program. SGPT levels were measured using the Clima MC-15 photometer. Two conditions were tested: monoreagent used immediately after mixing and monoreagent stored for 5 days at room temperature. Data were analyzed using the Shapiro-Wilk normality test and because the data were not normally distributed, the Wilcoxon test was used. The results showed that the average SGPT level using the immediate monoreagent was 10.69 U/L, while the delayed monoreagent showed an average of 9.88 U/L. Of the 16 samples, 9 decreased, 3 increased, and 4 remained unchanged. The Wilcoxon test produced a significance value of 0.030 (p < 0.05), indicating a statistically significant difference between the two conditions.In conclusion, there is a significant difference in SGPT levels immediate monoreagent use and delayed monoreagent use for 5 days at room temperature. It is recommended that monoreagent be used immediately after mixing to maintain accurate examination results.